A novel identification method for micro-vibration analysis of reaction wheel assembly. (July 2022) - Yang, Lin; Wang, Yan-song; Wei, Lei
Abstract: The disturbance forces/torques generated during the operation of the space born mechanisms and reaction wheel assembly with bearings, decrease the accuracy of satellite pointing and stabilization, resulting in distortion and blurring of the acquired images taking remote sensing satellite as an example. Therefore, studying the time-varying micro-vibration characteristics is critical to improve the performance of the spacecraft system. This paper proposes an identification method for bearing characteristic frequencies and modal frequencies, to study the distribution patterns and peak points of the disturbance forces/torques of the reaction wheel assembly. Firstly, time-frequency analysis is used to obtain the distribution of disturbance forces/torques signals at variable speeds. Then a method of bearing characteristic frequencies identification in harmonic domain is presented by function dimension reduction, to help recognize the primary bearing characteristic frequencies. Secondly, to address the time/speed-varying features, a parameterized matrix fraction equation containing the rotational speed is established. The unknown parameters of the equation are solved utilizing the weighted nonlinear least-squares estimation method and are converted into modal parameters. By combining the bearing characteristic frequency parameters and the modal frequency parameters, the continuous variation cloud diagram of the disturbance forces/torques under the speed-frequency coordinate can be described. Finally, an experimental case is carried out and the method was successfully applied to the analysis of the micro-vibration characteristics of a set of reaction wheel assemblies. The traditional modal parameters identification experiment is carried out at discrete constant speed with different step lengths as contrast. The results indicate that the method proposed in this paper can obtain more micro-vibration characteristic information than constant methods and is applicable for disturbance research of spacecrafts. Highlights: A dimension reduction method in harmonic domain is proposed to identify harmonics. A modal parameter identification method varying with speed of RWA is proposed. The proposed method helps to predict peak points of disturbing forces/torques. Validation and contrast experiments are carried out and results provide good proof.